Pharmacokinetic Drug-Drug Interactions and Herb-Drug Interactions - Min-Koo Choi; Im-Sook Song (MDPI AG, 2021)
Due to the growing use of herbal supplementation-ease of taking herbal supplements with therapeutics drugs (i [...]